Analisis Anatomi Gerakan Kontra Rencana Pembangunan Megaproyek PLTU Kabupaten Batang - saputro, Mohamad hijrah; ., Sulistyowati; setiyono, Budi (Journal of Politic and Government Studies, 2014)
Steam power plant is a plant that relies on the kinetic energy of steam toproduce electricity. Power plant is an alternative solution to solve the problem ofelectricity in Indonesia. Batang power plant is one national project that goes inMP3EI (Master Plan for the Acceleration of Indonesian Economic DevelopmentEquity). Social Movement UKPWR and Go Green rejected the plan to build theBatang’s steam power plant. This study aims to analyze the anatomy of the Batang’splant cons movement of both types of movement to movement activities.This study used qualitative methods to understand and interpret the meaningof an event interaction of human behavior in specific situations according to theperspective of researches. The collection data techniques that authors use in this studyare interviews and literature.The results showed that the power plant was built near Batang RegionalMarine protected areas using land between 370 to 700 acres and to cost up to 40trillion. Being rejected by local residents who are members of social movements intoUKPWR is an abbreviation of 5 villages affected Batang’s power plant. Residentsfear the impact caused by the power plant. NGOs working in the field of environmentis Go Green also rejected the power plant construction site which they are productivelands and areas that need to be conserved. The existence of the various protestedmake the development process is blocked until 3 years old.Keywords: Power Plant, Social Movements, NGOs, Civil Society Organizations